OBESITY - DEPRESSION INTERRELATION IN CHILDREN AND ADOLESCENT - Anamaria Ciubara; Lucian Stefan Burlea; Dana-Teodora; Marin Burlea; Ilinca Untu (Amaltea Medical Publishing House, 2014)
Obesity and depression represent two fundamental problems of public health at a global level; paediatric obesity is alarming both per se and through the risk of maintaining the obese status in adulthood and of continuing to be exposed to comorbidity, implicitly. On the other hand, depressionin childrenis a genuine diagnostic problem (considering its masked clinical symptomatology) and a diagnostic necessity (considering its severe consequences and mostly the pathological alterations of food-related behaviour). This paper seeks to elaborate a synthesis of the current scientifi c literature regarding the causes of obesity - depression comorbidities in children,with a focus on the interrelation and common etiopathogenic origin.